What is harmed by relationship can be healed by relationship: a developmental/relational approach to residential treatment for young children - Elizabeth Kohlstaedt (Scottish Journal of Residential Child Care)
Children whose earliest relationships have been marred by violence, chaos, abuse, neglect and loss find that these experiences are ‘hard-wired’ into their brain. As a result, they will grow up believing that these negative experiences reflect what future relationships will be like. Their way of seeing and interacting with the world has been permanently altered by their earliest adverse experiences. Treatment – with a known healing agent, administered in adequate dose and for adequate time and with adequate intensity – can bring those children back into relational health. The curative factor is a relationship with direct care staff. In this paper, the author will describe a developmental/relational approach to residential care for children which has been used at Intermountain, a treatment facility in Helena, Montana, USA, for 27 years. A description of the approach, a case example and the necessity of supervising and monitoring staff are provided. Outcomes of this approach are also detailed.